Answer: The base of the square is 52.67
Step-by-step explanation:
256=1/2bh
b=base
h=height
256=1/2(12)b
256=6b
52.67=b
Sharon drove 188.3 miles to see a softball game. If she was driving for 3 1/2 hours,what was her average rate of speed?
Answer:
The average rate of speed = 53.8 mph
Step-by-step explanation:
Sharon drove 188.3 miles.
She was driving for 3 1/2 hours = 7/2 = 3.5hours
To find the average speed simply divide the miles she drove by driving hours:
188.3/3.5
53.8 mph.
Therefore the average rate of speed = 53.8 mph....
A rain gutter is to be constructed of aluminum sheets 12 inches wide. After marking off a length of 4 inches from each edge, this length is bent up at an angle θ. The area A of the opening may be expressed as the function: A(θ) = 16 sin θ ⋅ (cos θ + 1). If θ = 45°, what is the area of the opening?
Answer:
[tex]4(2+\sqrt{2})\text{ square unit}[/tex]
Step-by-step explanation:
Given function that shows the area of the opening,
[tex]A(\theta)=16 \sin\theta (\sin \theta + 1)[/tex]
If [tex]\theta = 45^{\circ}[/tex]
Hence, the area of the opening would be,
[tex]A(45^{\circ})=16 \sin 45^{\circ} (\cos 45^{\circ} + 1)[/tex]
[tex]=16\times \frac{1}{\sqrt{2}}\times (\frac{1}{\sqrt{2}}+1)[/tex]
[tex]=16(\frac{1}{2}+\frac{1}{\sqrt{2}})[/tex]
[tex]=8+\frac{16}{\sqrt{2}}[/tex]
[tex]=8+4\sqrt{2}[/tex]
[tex]=4(2+\sqrt{2})\text{ square unit}[/tex]
At one college, GPA's are normally distributed with a mean of 2.9 and a standard deviation of 0.6. Using the empirical rule, what percentage of students at the college have a GPA between 2.3 and 3.5? 84.13% 68% 99.7% 95%
Answer:
68%
Step-by-step explanation:
According to the empirical rule:
68% of the data values lie within one standard deviation from the mean i.e. from z = -1 to z = 1 we have 68% of the data values95% of the data values lie within two standard deviations of the mean99.7% of the data values lie within three standard deviations of the meanSo first we have to find how many standard deviations away from the mean are the given two values. This can be done by converting them into z scores.
The formula to calculate the z-score is:
[tex]z=\frac{\text{Data Value}-\text{Mean}}{\text{Standard Deviation}}[/tex]
Using the given values in above formula, we get:
For x = 2.3
[tex]z = \frac{2.3-2.9}{0.6}=-1[/tex]
For x = 3.5
[tex]z = \frac{3.5-2.9}{0.6}=1[/tex]
This means we have to tell how many data values are within one standard deviation of the mean. According to the empirical rule 68% of the values are between z= -1 and z = 1. So the answer is 68%
68% of students at the college have a GPA between 2.3 and 3.5.
What is the empirical rule?The empirical rule states that for a normal distribution, 68% of the values falls within one standard deviation, 95% of the values falls within two standard deviation, and 99.7% of the values falls within three standard deviation.
Hence:
For a mean of 2.9 and a standard deviation of 0.6.
68% falls within 2.9 ± 0.6 = (2.3, 3.5)
68% of students at the college have a GPA between 2.3 and 3.5.
Find out more on empirical rule at: https://brainly.com/question/10093236
If 20 is added to the number, the absolute value of the result is 6.
Answer:
(20+x)*2=x-6
40+2x=x-6
40=-x-6
46=-x
check:
x=-46
20-46*2=-46-6
-26*2=-52
-52=-52
x=-46
Answer:
x1=-14;x2=-26
Step-by-step explanation:
|x+20|=6
x+20=6
x+20=-6
If this is the graph of f(x) = a^(x+h)+k
Answer:
C. 0 < a < 1Step-by-step explanation:
[tex]\text{For}\ f(x)=a^{(x+h)}+k\\\\\text{always}\ a>0\\\\\text{If}\ a>1,\ \text{then the function is increasing}\\\\\text{If}\ 0<a<1,\ \text{then the function is decreasing}\\\\<-h,\ k>-\text{translation vector}\\\\============================[/tex]
[tex]\text{From the graph:}\\\\\text{the function is decreased}\to 0<a<1\\\\h<0\\\\k>0[/tex]
The correct answer is: Option: C
C. 0<a<1
Step-by-step explanation:We are given a graph of a exponential function as:
[tex]f(x)=a^{x+h}+k[/tex]
We know that the function is a exponential decay function if: 0<a<1
and it represents a exponential growth function if: a>1
Hence, by looking at the graph we observe that the graph is continuously decreasing with increasing values of x.
This means that the graph is a graph of exponential decay function.
Hence, we get: 0<a<1
A.-1/3
B.-1
C.-3/2
D.-2/3
Answer:
Hi there!
The answer to this question is: C. -3/2
Step-by-step explanation:
You first find the slope of the equation using the change of y over the change of x formula. You should get 2/3. Then it asks its perpendicular that is simply the negative reciprocal of the original slope. All you do is flip the fraction and make it negative, your final answer should be -3/2
Answer:
C
Step-by-step explanation:
Calculate the slope m using the slope formula
m = (y₂ - y₁ ) / (x₂ - x₁ )
with (x₁, y₁ ) = (- 3, - 1 ) and (x₂, y₂ ) = (3, 3)
m = [tex]\frac{3+1}{3+3}[/tex] = [tex]\frac{4}{6}[/tex] = [tex]\frac{2}{3}[/tex]
Given a line with slope m then the slope of a line perpendicular to it is
[tex]m_{perpendicular}[/tex] = - [tex]\frac{1}{m}[/tex] = - [tex]\frac{1}{\frac{2}{3} }[/tex] = - [tex]\frac{3}{2}[/tex] → C
The circle below is centered at the point (8,4) and has a radius of length 4 what is the equation
[tex]\bf \textit{equation of a circle}\\\\ (x- h)^2+(y- k)^2= r^2 \qquad center~~(\stackrel{8}{ h},\stackrel{4}{ k})\qquad \qquad radius=\stackrel{4}{ r} \\\\[-0.35em] ~\dotfill\\\\ (x-8)^2+(y-4)^2=4^2\implies (x-8)^2+(y-4)^2=16[/tex]
Answer:
wht are da choices
Step-by-step explanation:
the simplified expression
Answer:
[tex]5x^2 y^2[/tex]
Step-by-step explanation:
We need to use the properties shown below to solve this:
1. [tex]\sqrt[n]{x^a} =x^{\frac{a}{n}}[/tex]
2. [tex]\sqrt{x}\sqrt{x} =x[/tex]
3. [tex]\sqrt{x} \sqrt{y}=\sqrt{x*y}[/tex]
Area of a triangle is given by 1/2 * base * height, so we do that and simplify:
[tex]A=\frac{1}{2}(\sqrt{5x^3} )(2\sqrt{5xy^4} )\\A=\frac{1}{2}(5x^3)^{\frac{1}{2}}*2*(5xy^4)^{\frac{1}{2}}\\A=\sqrt{5}x^{\frac{3}{2}}*\sqrt{5}\sqrt{x} } y^2\\A=\sqrt{5} \sqrt{5}x^{\frac{3}{2}} x^{\frac{1}{2}}y^2\\A=5*x^2y^2\\A=5x^2 y^2[/tex]
Factor completely 10x5 + 4x4 + 8x3.
Answer:
Step-by-step explanation:
2x3 out of 10x5+4x4+8x3.2x3(5x2+2x+4)
Answer:
2*5*5 +2*2*2*2 + 2*2*2*3
Step-by-step explanation:
Does (99, -16) make the equation y = 3x – -51 true?
ayes
Answer:
No this is not a solution
Step-by-step explanation:
Substitute the points in and see if the equation is true
-16 = 3(99) - -51
-16 = 297+51
-16 =348
False, so this is not a solution
Could some one help me solve this please ?
Answer:
Step-by-step explanation:
Later on in the course, I hope you are told that answers should not rely on diagrams.
Since you have to answer the question somehow, the answer (directly) is BCA. Since this is an appearance question (that's what the answer looks like), you can only state the answer, There really (in this case) is no what to offer a proof).
Suppose f(x) = x. Find the graph of f(x) +2.
Click on the correct answer.
graph 1
graph 2
graph 3
graph 4
Answer:
graph 2
Step-by-step explanation:
It is partially written in Slope-Intercept Form [y = mx + b]. That 2 tells you to move up two units.
If you are ever in need of assistance, do not hesitate to let me know by subscribing to my channel [USERNAME: MATHEMATICS WIZARD], and as always, I am joyous to assist anyone at any time.
The graph of f(x) +2 graph 3.
since y-intercepts is 2
The answer is option C
What is a straight line graph?The graph follows a straight line equation shows a straight line graph.equation of a straight line is y=mx+cy represents vertical line y-axis.x represents the horizontal line x-axis. m is the slope of the lineslope(m)=tan∅=y axis/x axis.
c represents y-intercepts (it is the point at which the line cuts on the y-axis)Straight line graphs show a linear relationship between the x and y values.Learn more about the straight lines here:-https://brainly.com/question/14323743
#SPJ2
(6,3) graph of f(x) find the point of for the function f(-1/2x).
Answer:
(-12,3)
Step-by-step explanation:
Since (6,3) is on the graph of f(x), then f(6)=3.
We want to see if we can use f(6)=3 to find a point on the graph of f(-1/2x).
If you compare -1/2x to 6, what must x be so they have the same value? x=-12.
If that wasn't obvious to you, just solve:
-1/2x=6
Multiply both sides by -2:
x=-12
So if we replace x with -12 in f(-1/2x) we get
f(-1/2*-12)
f(6)=3
And we were given this f(6)=3 so f(-1/2*-12)=3.
How do I find the mistake the student did?
Answer:
Step-by-step explanation:
What he did at the end of the given equations is solve for x in x + 8y= 21
x = 21 - 8y Substitute that result in the top equation.
7(21 - 8y) + 5y = 14 is the correct step To continue Remove the brackets
147 - 56y + 5y = 14 Combine
147 - 51y = 14 Add 51y to both sides.
147 = 51y + 14 Subtract 14 from both sides.
133 = 51y divide by 51
y = 2.61 rounded.
The incorrect step is underlined and italicized.
What is the solutions to the equation below x^2+10x+25=2
If there are more then one that’s ok
Answer:
[tex]x1=-5+\sqrt{2} \\x2=-5-\sqrt{2}[/tex]
Step-by-step explanation:
First we need to simplify your equation by grouping coefficients:
[tex]x^{2} +10x+23=0[/tex]
Now, there are two valid values for your variable, wich are determined by the following expressions:
[tex]x=\frac{-b+\sqrt{b^{2}-4ac } }{2a} \\\\x=\frac{-b-\sqrt{b^{2}-4ac } }{2a}[/tex]
We will call those expression as (eq1) and (eq2) in their respective order
In both scenarios the following is derived from your grouped equation.
[tex]a=1\\b=10\\c=23[/tex]
[tex]x1=\frac{-10+\sqrt{10^{2}-4*1*23 } }{2*1}\\x2=\frac{-10-\sqrt{10^{2}-4*1*23 } }{2*1}[/tex]
[tex]x1=\frac{-10+\sqrt{8 } }{2}\\\\x2=\frac{-10-\sqrt{8} }{2}[/tex]
We can simplify these expressions a little more by doing the following
[tex]x1=\frac{-10+2 \sqrt{2 } }{2}\\\\x2=\frac{-10-2\sqrt{2} }{2}[/tex]
The result is
[tex]x1=-5+\sqrt{2} \\x2=-5-\sqrt{2}[/tex]
We can not simplify these expresions anymore
What is the equation in point-slope form of the line passing through (0, 5) and (−2, 11)? y − 5 = −3(x + 2) y − 5 = 3(x + 2) y − 11 = −3(x − 2) y − 11 = −3(x + 2)
Answer:
y - 11 = - 3(x + 2)
Step-by-step explanation:
The equation of a line in point- slope form is
y - b = m(x - a)
where m is the slope and (a, b) is a point on the line
Calculate m using the slope formula
m = (y₂ - y₁ ) / (x₂ - x₁ )
with (x₁, y₁ ) = (0, 5) and (x₂, y₂ ) = (- 2, 11)
m = [tex]\frac{11-5}{-2-0}[/tex] = [tex]\frac{6}{-2}[/tex] = - 3
Use either of the 2 given points for (a, b)
Using (a, b) = (- 2, 11), then
y - 11 = - 3(x - (- 2)), that is
y - 11 = - 3(x + 2)
PLEASE ANSWER CORRECTLY
PLEASE HURRY
WILL GIVE BRAINLIEST
An ellipse is represented using the equation . Where are the foci of the ellipse located? Check all that apply.
(−29, 7)
(19, 7)
(−21, 7)
(13, 7)
(−5, −17)
(−5, 31)
EQUATION:
Answer:
Options A and B.
Step-by-step explanation:
An ellipse is represented by the equation [tex]\frac{(x+5)^{2}}{625}+\frac{(y-7)^{2}}{49}=1[/tex]
We have to find the foci of the given ellipse.
Ellipse having equation [tex]\frac{(x-h)^{2}}{a^{2} }+ \frac{(y-k)^{2} }{b^{2} }=1[/tex]
Then center of this ellipse is represented by (h, k) and foci as (c, 0) and (-c, 0).
And c is represented by c² = a² - b²
So we co relate this equation with our equation given in the question.
a = √625 = 25
b = √49 = 7
and c² = (25)² - (7)²
c² = 625 - 49 = 576
c = ±√576
c = ±24
Now we know center of the ellipse is at (-5, 7) so foci can be obtained by adding and subtracting x = 24 from the coordinates of the center.
Center 1 will be [(-5+24=19), 7] ≈ (19, 7)
Center 2 will be [(-5-24=-29), 7] ≈ (-29, 7)
Therefore, options A and B are correct.
Answer:
A and B
Step-by-step explanation:
x^2+2x+1 is a perfect square trinomial
True of False?
Answer:
True.
Step-by-step explanation:
It is because it is in the form [tex]a^2x^2+2abx+b^2[/tex] and this equals [tex](ax+b)^2[/tex].
Why it is in that form: well comparing [tex]a^2x^2+2abx+b^2[/tex], we have [tex]a=1, b=1[/tex]. Testing, plug in those values:
[tex](1)^2x^2+2(1)(1)x+(1)^2[/tex]
[tex]1x^2+2x+1[/tex]
[tex]x^2+2x+1[/tex].
This has the squared form of [tex](x+1)^2[/tex].
Test if you like:
[tex](x+1)^2[/tex]
[tex](x+1)(x+1)[/tex]
Use foil to expand:
First: x(x)=x^2
Outer: x(1)=x
Inner: 1(x)=x
Last: 1(1)=1
---------------Add together
[tex]x^2+2x+1[/tex]
It does indeed equal.
The measure of arc AB is
The measure of angle AOB is
The measure of angle BDA is
Answer:
Part 1) The measure of arc AB is 50°
Part 2) The measure of angle AOB is 50°
Part 3) The measure of angle BDA is 25°
Step-by-step explanation:
step 1
Find the measure of arc AB
we know that
arc AD+arc BD+arc AB=360° -----> by complete circle
substitute the given values
212°+98°+arc AB=360°
310°+arc AB=360°
arc AB=360°-310°=50°
step 2
Find the measure of angle AOB
we know that
The measure of angle AOB is the same that the measure of arc AB by central angle
so
m∠AOB=arc AB=50°
step 3
Find the measure of angle BDA
we know that
The inscribed angle measures half that of the arc comprising
so
m∠BDA=(1/2)[arc AB]
we have
arc AB=50°
substitute
m∠BDA=(1/2)[50°]=25°
The arc of a circle is defined as the part or segment of the circumference of a circle.
The measure of arc AB is 50 degrees.
An angle of a circle is an angle that is formed between the radii, chords, or tangents of a circle.
The measure of angle AOB is 50 degrees.
The measure of angle BDA is 25 degrees.
We have to determineThe measure of arc AB is
The measure of angle AOB is
The measure of angle BDA is
What is an arc?The arc of a circle is defined as the part or segment of the circumference of a circle.
What is the angle?An angle of a circle is an angle that is formed between the radii, chords, or tangents of a circle.
1. The measure of arc AB is,
[tex]\rm Arc \ AD+Arc \ BD+Arc \ AB=360\\\\212+98+Arc\ AB=360\\\\310+Arc \ AB=360\\\\ Arc \ AB=360-310\\\\ Arc\ AB = 50[/tex]
The measure of arc AB is 50 degrees.
2. The measure of angle AOB is,
[tex]\rm m\angle \ AOB=Arc \ AB=50 degrees[/tex]
The measure of angle AOB is 50 degrees.
3. The measure of angle BDA is,
[tex]\rm m \angle BDA=\dfrac{1}{2}\times Arc AB\\\\ m \angle BDA=\dfrac{1}{2}\times 50\\\\ m \angle BDA = 25[/tex]
The measure of angle BDA is 25 degrees.
To know more about Arc and Angle click the link given below.
https://brainly.com/question/8726843
Determine whether the statement is true or false. -3 ≥ -15
let's recall that, on the number line, for the positive side, the farther from zero, the larger the number, thus 100 is a much larger number than 10.
now, on the negative side of the number line, the farther from zero, the smaller the number, thus -1 is much much larger number than -1,000,000,000.
is -3 ≥ -15, is -3 larger or equals to -15, well, certainly is not equal but is certainly larger, yes.
You deposit $500 into a bank account that pays 2% simple interest. You leave the money in the account for 3 years and no additional money is added or withdrawn. How much money will you have in the account at the end of the three ywars? (The formulafor simple interest is I=Prt)
[tex]\bf ~~~~~~ \textit{Simple Interest Earned} \\\\ I = Prt\qquad \begin{cases} I=\textit{interest earned}\\ P=\textit{original amount deposited}\dotfill & \$500\\ r=rate\to 2\%\to \frac{2}{100}\dotfill &0.02\\ t=years\dotfill &3 \end{cases} \\\\\\ I=(500)(0.02)(3)\implies I=30~\hfill \stackrel{\textit{total amount in the account}}{500+30\implies 530}[/tex]
What is the simplest form of 2√3/√6
Answer is A On edgu
Answer:
[tex] \sqrt{2}[/tex]
Step-by-step explanation:
You can multiply by sqrt 6/sqrt 6 to get rid of the sqrt in the denominator. This leaves you with 2(sqrt 3)(sqrt 6)/sqrt 36. The sqrt's in the numerator can be multiplied to get 2(sqrt 18). The sqrt 36 can be simplified to just 6. Sqrt 18 can be split into sqrt 9 and sqrt 2. The sqrt 9 can be taken out and simplified as 3. 3x2=6. This leaves you with 6(sqrt 2)/6. The 6 in the numerator cancels the 6 in the denominator and just leaves sqrt 2.
Answer:
aaaaaaaaaaa
Step-by-step explanation:
Pick the correct description of the line x = -5
Answer:
see explanation
Step-by-step explanation:
The line with equation x = - 5
Is a vertical line parallel to the y- axis and passing through all points with an x- coordinate of - 5
4. What is the value of x in the equation below?
14.3 -0.4x = 2.6x + 5.6
Answer:
x = 2.9.
Step-by-step explanation:
14.3 - 0.4x = 2.6x + 5.6
14.3 - 5.6 = 2.6x + 0.4x
8.7 = 3x
x = 8.7 / 3 = 2.9 (answer).
Answer:
x=2.9
Step-by-step explanation:
14.3 -0.4x = 2.6x + 5.6
Add .4x to each side
14.3 -0.4x+.4x = 2.6x+.4x + 5.6
14.3 = 3x+5.6
Subtract 5.6 from each side
14.3 - 5.6 = 3x - 5.6
8.7 =3x
Divide each side by 3
8.7/3 = 3x/3
2.9=x
To find 'd' choose one calculation:
Answer:
[tex]\sqrt{7^{2}+5^{2} }[/tex]
Step-by-step explanation:
Since the whole base of the triangle is 14, we can half it to find the base of one triangle which is 7.
Pythagoras Theorem states a² + b² = c²
In this case a² = 7 and b² = 5 so,
a² + b² = c²
a² = 7 and b² = 5
7² + 5² = c²
49 + 25 = c²
74 = c²
√74 = c
choose the equation that represents the line passing through the point -3,-1 with a slope of 4
y=4x-11
y=4x+11
y=4x+7
y=4x-7
Answer:y=4x+11
Step-by-step explanation:
Substitute the coordinates in each of the above equations,
Then the left hand side of the equation should be equal to the right hand side of the equation.
By substituting the above coordinates in the second answer,
-1= 4(-3)+11
-1=-1
Answer:
b
Step-by-step explanation:
-50 Points-
Find the distance from point B to point C.
Enter as a decimal rounded to the nearest tenth.
Using the law of Tangents:
Tan(angle) = Opposite leg / Adjacent leg.
Using the provided information:
Tangent (61) = BC / 5.7
Solve for BC:
BC = 5.7 x tangent(61)
BC = 10.3 miles ( rounded to the nearest tenth).
The distance from point B to point C is 10.3 mi (to the nearest tenth).
What is the trigonometric ratio formula for tan function ?
If we have a right angle triangle,
Then, tanθ = Opposite side/ Adjacent side
What is the required distance ?Here in the right angle triangle ABC,
Adjacent side = AB = 5.7 mi
θ = 61°
We have to find the BC.
∴ tanθ = Opposite side/ Adjacent side
⇒ tanθ = BC/AB
⇒ tan61°= BC/5.7
⇒ BC = 5.7×tan61°
⇒ BC = 10.283 = 10.3 (to the nearest tenth)
Learn more about measuring distance here :
https://brainly.com/question/11208407
#SPJ2
Find the GCF of 21, 63 and 105.
Answer:
21
Step-by-step explanation:
To find the greatest common factor between a set of numbers, you can list the factors of those numbers and find the largest one they each have in common.
A factor of a number is a number which can be multiplied against another number to get your original number.
Factors of 21: 1, 3, 7, 21
Factors of 63: 1, 3, 7, 9, 21, 63
Factors of 105: 1, 3, 5, 7, 15, 21, 35, 105
21 is the greatest factor which all three have in common.
Answer:
21
Step-by-step explanation:
GCF of 21, 63 and 105
Break these numbers into prime factors
21 = 3*7
63 = 9*7 = 3*3*7
105 = 15*7 = 3*5*7
There is a 3, 7 in all the terms
The largest number of 3's in the terms is 1
The largest number of 7's is 1
Multiply the largest number of terms together
3*7 =21
HELP!!!!!ASAP!!!!!!
A right triangle in which one acute angle is a reference angle for a
115°
angle in standard position intersects the unit circle at
(−0.423,0.906)
. What is the approximate value of
sin115°≈
Answer:
[tex]\sin( 115 \degree) = 0.906[/tex]
Step-by-step explanation:
The general point on a unit circle is given by
[tex]x = \cos( \theta) [/tex]
[tex]y = \sin( \theta) [/tex]
where
[tex] \theta = 115 \degree[/tex]
is the terminal side of the angle in standard position.
Therefore
[tex]x = \cos( 115 \degree) [/tex]
[tex]y = \sin(115 \degree) [/tex]
lies on this circle
This angle intersects the unit circle at
[tex]( - 0.423,0.906)[/tex]
Hence we must have
[tex] \cos( 115 \degree) = - 0.463[/tex]
[tex]\sin( 115 \degree) = 0.906[/tex]
I don’t wanna fail math :( pls help will mark brainliest!! I used all my points so here 15. Pls help me
Answer:
D
Step-by-step explanation:
First, find the slope using the slope formula. The slope is 3.
Now plug in any of the x and y values and the value of the slope into the slope-intercept form equation to solve for b.
9=3(3)+b, solve for b
b=0, Now convert the equation y=3x into slope-intercept form.
y-9=3(x-3) This is the equation of the line, the plant will be about 36 cm tall after 12 months.